Wars, Trees and the Struggle for Peace - Mehdi, Syed Sikander (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
The historical, spiritual, environmental and humanistic properties of trees are recognized worldwide. As a matter of fact, the recognition of their value as an asset to the entire humanity has increased with the passage of time. Their importance has been highlighted not only by the holy books and spiritual leaders of different religions but also by the story tellers, poets, novelists, painters, film makers, medicine manufacturers, and environmental activists. With the growing awareness of the causes and consequences of climate change, proliferating scientific studies have been projecting tree plantation and forestation as an existential need. However, the ruination of trees due to wars and violence doesn’t seem to have received as much global attention as it should have. Perhaps it won’t be an exaggeration to say that a comprehensive peace perspective on the trees hasn’t been fully developed yet. The destruction of hundreds of thousands of trees in wars and violence are rarely noticed, and voices affirming that the trees also have a right to life and protection in wars and warlike situations as humans are supposed to have are still very mute. This paper discusses the sufferings of the trees as wars victims. It emphasizes the need for a worldwide campaign in favor of the basic rights of the trees and asks as to how can the campaign for the rights of the trees be converted into a powerful agency and how can the worldwide struggle for peace benefit from such an agency.